Fabrication, characterization, and properties of poly(ethylene‐co‐vinyl acetate)/magnetite nanocomposites. Issue 7 (14th November 2013) - Ramesan, M. T.
ABSTRACT Poly(ethylene‐co‐vinyl acetate) (EVA)/magnetite (Fe3O4) nanocomposite was prepared with different loading of Fe3O4 nanoparticles. The mixing and compounding were carried out on a two‐roll mixing mill and the sheets were prepared in a compression‐molding machine. The effect of loading of nanoparticles in EVA was investigated thoroughly by different characterization technique such as transmission electron microscopy (TEM), X‐ray diffraction (XRD), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), limiting oxygen index (LOI), and technological properties. TEM analysis showed the uniform dispersion of filler in the polymer matrix and the dispersion of filler decreased with increase in filler content. XRD of the nanocomposite revealed the more ordered structure of the polymer chain. An appreciable increase in glass transition temperature was observed owing to the restricted mobility of Fe3O4‐filled EVA nanocomposite. TGA and flame resistance studies indicated that the composites attain better thermal and flame resistance than EVA owing to the interaction of filler and polymer segments. Mechanical properties such as tensile strength, tear resistance, and modulus were increased for composites up to 7 phr of filler, which is presumably owing to aggregation of Fe3O4 nanoparticle at higher loading. The presence of Fe3O4 nanoparticles in the polymer matrix reduced the elongation at break and impact strength while improved hardness of the composite than unfilled EVA. The change in technological properties had been correlated with the variation of polymer–filler interaction estimated from the swelling behavior. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40116.